2016
DOI: 10.1186/s12936-016-1629-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium malariae in the Colombian Amazon region: you don’t diagnose what you don’t suspect

Abstract: BackgroundMalaria is a worldwide public health problem; parasites from the genus Plasmodium spp. are the aetiological agent of this disease. The parasite is mainly diagnosed by microscope-based techniques. However, these have limited sensitivity. Many asymptomatic infections are sub-microscopic and can only be detected by molecular methods. This study was aimed at comparing nested PCR results to those obtained by microscope for diagnosing malaria and to present epidemiological data regarding malaria in Colombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
(87 reference statements)
0
18
1
Order By: Relevance
“…For achieving the ultimate goal of eliminating malaria in Kenya, existing control programs that primarily target P. falciparum are inadequate. The use of rapid diagnostic tests or microscopy as first-line diagnostic methods can lead to gross underestimation of the actual prevalence of P. malariae ( 4 6 ). Our findings indicated that P. malariae accounted for ≈3% of clinical cases and ≈5% of asymptomatic infections in this malaria-endemic region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For achieving the ultimate goal of eliminating malaria in Kenya, existing control programs that primarily target P. falciparum are inadequate. The use of rapid diagnostic tests or microscopy as first-line diagnostic methods can lead to gross underestimation of the actual prevalence of P. malariae ( 4 6 ). Our findings indicated that P. malariae accounted for ≈3% of clinical cases and ≈5% of asymptomatic infections in this malaria-endemic region.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, P. malariae and P. ovale receive little attention, and malaria caused by these organisms is among the most neglected tropical diseases ( 3 ). In those rural areas of Africa where malaria is most common, affordable diagnostic tools are rapid diagnostic tests and microscopy, but they are not effective for detecting these 2 species, mainly because parasitemia with these species is low ( 4 6 ). As a result, P. malariae and P. ovale infections are often underestimated, and epidemiologic information, such as distribution and prevalence of these species in malaria-endemic areas, is lacking.…”
mentioning
confidence: 99%
“…P. malariae deploys a different transmission strategy, with a large parasite reservoir in asymptomatic carriers with low parasitemia. These chronic P. malariae infections can occasionally cause anemia and nephrotic syndrome (4,(6)(7)(8). Use of molecular techniques such as qPCR has enabled more sensitive detection of parasite carriage compared to microscopy (3,9).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmodium malariae deploys a different transmission strategy, with a large parasite reservoir in asymptomatic carriers with low parasitaemia. These chronic P. malariae infections can occasionally cause anaemia and nephrotic syndrome [4,[6][7][8]. Use of molecular techniques such as qPCR has enabled more sensitive detection of parasite carriage compared to microscopy [3,9].…”
mentioning
confidence: 99%